2010
DOI: 10.1111/j.1752-699x.2010.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional prediction of moderate to severe obstructive sleep apnoea

Abstract: Introduction: Upper airway inflammation and narrowing are characteristics of obstructive sleep apnoea (OSA). Inflammatory markers have been found to be increased in exhaled breath and induced sputum of patients with OSA. Objectives: The aim of this study was to investigate if the measurement of exhaled nitric oxide (FENO), as marker of airway inflammation, together with the forced mid-expiratory/mid-inspiratory airflow ratio (FEF50/FIF50), as marker of upper airway narrowing, may help to predict OSA. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…In contrast, two studies by the same group demonstrated that FE NO levels were higher in OSA compared only to non-obese healthy volunteers [5,23]. FE NO A recent study concluded that FE NO has only limited clinical potential in the screening of sleep disordered breathing (SDB) [41], however a composite index including BMI, age, carboxy-haemoglobin saturation, FEF 50 /FIF 50 , neck circumference and FE NO was predictive for OSA [42]. In children, both OSA and non-OSA subjects, habitual snoring appears to be associated with higher FE NO levels [31].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 78%
“…In contrast, two studies by the same group demonstrated that FE NO levels were higher in OSA compared only to non-obese healthy volunteers [5,23]. FE NO A recent study concluded that FE NO has only limited clinical potential in the screening of sleep disordered breathing (SDB) [41], however a composite index including BMI, age, carboxy-haemoglobin saturation, FEF 50 /FIF 50 , neck circumference and FE NO was predictive for OSA [42]. In children, both OSA and non-OSA subjects, habitual snoring appears to be associated with higher FE NO levels [31].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 78%
“…Besides, our study also had some advantages such as using LASSO regression for analyzing clinical factors, 10-fold subjects than previous study and had validation group. Other studies also used clinical nomograms to calculate AHI and even estimate median survival time/event-free survival [7, 22]. We will also extend the usage of nomograms in OSA in further prospective studies.…”
Section: Discussionmentioning
confidence: 96%
“…Sleep apnea, despite being the most common reason for EDS, was not considered to be a useful clinical feature for detecting OSAS in patients because 30 to 50% of the society claim moderate to sleepiness [ 1 , 2 ]. In addition, other sleep disorders and diseases may cause EDS.…”
Section: Discussionmentioning
confidence: 99%
“…However, in-lab PSG's limited availability, its high cost, and time- and labor-consuming nature are its disadvantages. The waiting lists of sleep clinics for PSG are quite long, and it is difficult to perform PSG on all patients suspected of OSAS [ 2 ]. Thus, many studies that aim to diagnose OSAS via clinical findings and easily applicable tests have been carried out.…”
Section: Introductionmentioning
confidence: 99%